Factors affecting superovulation induction in goats (Capra hericus): An analysis of various approaches - Khan, Samiullah; Jamal, Muhammad Ameen; Khan, Ibrar Muhammad; Ullah, Irfan; Jabbar, Abdul; Khan, Nazir Muhammad; Liu, Yong (Frontiers in Veterinary Science, 2023)
Goats are generally called a “poor man's cow” because they not only provide meat and milk but also other assistance to their owners, including skins for leather production and their waste, which can be used as compost for fertilizer. Multiple ovulation and embryo transfer (MOET) is an important process in embryo biotechnology, as it increases the contribution of superior female goats to breeding operations. The field of assisted reproductive biotechnologies has seen notable progress. However, unlike in cattle, the standard use of superovulation and other reproductive biotechnologies has not been widely implemented for goats. Multiple intrinsic and extrinsic factors can alter the superovulatory response, significantly restricting the practicability of MOET technology. The use of techniques to induce superovulation is a crucial step in embryo transfer (ET), as it accelerates the propagation of animals with superior genetics for desirable traits. Furthermore, the conventional superovulation techniques based on numerous injections are not appropriate for animals and are labor-intensive as well as expensive. Different approaches and alternatives have been applied to obtain the maximum ovarian response, including immunization against inhibin and the day-0 protocol for the synchronization of the first follicular wave. While there are several studies available in the literature on superovulation in cattle, research on simplified superovulation in goats is limited; only a few studies have been conducted on this topic. This review describes the various treatments with gonadotropin that are used for inducing superovulation in various dairy goat breeds worldwide. The outcomes of these treatments, in terms of ovulation rate and recovery of transferrable embryos, are also discussed. Furthermore, this review also covers the recovery of oocytes through repeated superovulation from the same female goat that is used for somatic cell nuclear transfer (SCNT).